(untitled) (Bangladesh Journal of Nutrition, 2012)
The present study has been undertaken to investigate plasma creatinine, folate and vitamin B12 as underlying factors in the reduction of plasma homocysteine concentration in different trimesters of pregnancy. Under a cross-sectional design, 30 healthy nonpregnant as well as 130 pregnant women, at 3 different trimesters of pregnancy (43 in 1st trimester, 44 in 2nd trimester and 43 in 3rd trimester) were sampled for plasma levels of folate, vitamin B12, homocysteine and creatinine. Plasma homocysteine and creatinine level were significantly (p<0.014) lower in pregnant women at different trimester (1st, 2nd and 3rd trimester) compared to nonpregnant women. Plasma folate was significantly higher in different groups of pregnant women compared to nonpregnant women. Significant negative correlation was found between plasma homocysteine and folate in nonpregnant (r=-0.453, p<0.012) and pregnant women at 2nd trimester (r=-0.681, p<0.001). There was found significant negative correlation between plasma homocysteine and vitamin B12 at 1st trimester group (r=-0.322, p<0.035) and 2nd trimester group (r=-0.394, p<0.008) but not in 3rd trimester. In present study, reduction of plasma total homocysteine appears to be a physiological response in pregnancy, and the level of plasma folate and vitamin B12, but can not be explained by renal homodynamic changes. DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12833 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.69-79